Motion Analysis (2007)
Sports medicine and performance analyses go hand in hand with analyses aimed at preventing injury. While the protocols are often very similar, the analysis of sports related movements often entails analyzing a variety of highly dynamic movements. The magnitudes for angular velocities and accelerations associated with sports activities are often large and occur while translating through large fields of view. Motion Analysis provides the tools for the Sports Medicine & Performance professional to perform accurate functional evaluations/analyses for clinical and research oriented purposes such as: